PENGEMBANGAN E-MODUL MENGGUNAKAN FLIPBOOK PADA SUBTEMA BENDA TUNGGAL DAN CAMPURAN - Resyi Abdul Gani Abdul Gani; Eka Suhardi; Azmi Mauladia Rahmani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
E-Module Development Using Single and Mixed SubThemes Flipbooks aims todetermine the feasibility of developing teaching materials. The researchmethodology used was research and development with the ADDIE model (Analyze,Design, Development, Implementation, Evaluation) with research subjects fromclass V-A SDN Dukuh 01. The instruments used in this research were validationsheets from media experts, linguists, and expert material with three experts, studentresponse instruments, and pre-test and post-test instruments. The validation resultsyielded an average of 96.3% with the criteria of "Very Eligible", then the results ofthe pre-test and post-test produced an N-Gain score of 0.59 with the criteria of"Moderate" and obtained 89% of student responses with the criteria of "Very Good".Based on the results obtained, the development of e-modules using flipbooks onsingle and mixed object sub-themes meets valid criteria.